ANALISIS IMPLEMENTASI PERATURAN MENTERI KEUANGAN N0.158/PERATURAN MENTERI KEUANGAN NO.04/2017 TENTANG PENGGUNAAN APLIKASI MANIFES BEA CUKAI PADA PROSES PENERBITAN DOKUMEN INWARD & DOKUMEN OUTWARD (STUDI KASUS PT. XYZ LOGISTICS INDONESIA) - Ajahlia, Yusniar Jannahti; Nahshir, Achsanul (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This  study  is  shown  to  analyze  the  procedure  for  implementing  the  regulation  of  the Minister  of Finance  No.  158  /  Regulation  of  the Minister  of  Finance  No.  04  of  2017  concerning  the process of issuing inward manifest and outward manifest documents at PT. XYZ Logistics. In the process  of  issuing  manifest  documents,  problems  often  arise  that  can  hinder  the  unloading  or transportation  of  goods.  These  problems  can  occur  due  to  errors  in  data  entry,  causing  the documents  to  be  redressed  by  customs,  manifest  documents  that  are  not  retrieved  for  data reconciliation,  and  delays  in  the  submission  of  manifest  documents.  This  research  is  qualitative with a descriptive approach. The determination of informants is based on employees who handle the issuance of manifest documents directly,  informants from  customs institutions,  and academic  informants  chosen  based  on  the  export-import  courses  they  teach.  The  results  of the  study  related  to  the  analysis  of  the  implementation  of  PMK  No.  158  PMK  No.04  of  2017 concerning  the  procedures  for  issuing  manifest  documents.  This  study  shows  that  PT.  XYZ Logistics  understands  the policy  in  PMK  No.  158  PMK  No.  4  of  2017  and  comprehends  the process  of  issuing  manifest  documents.  However,  in  practice,  there  are  still  frequent  errors  that cause  delays  in  the  submission  of  manifest  documents.  This  study  aims  to  identify  the  impact of  errors  in  the  process  of  issuing  manifest  documents  and  how  PT.  XYZ  Logistics  addresses the  problems  that  arise  in  the  process  of  issuing  manifest  documents  in  accordance  with  PMK No.  158  PMK  No.  04  of  2017.  Suggestions  that  can  be  proposed  include  increasing  awareness of the responsibilities given, enhancing human resources as export-import regulations or policies  can  change,  and  fostering  cooperation  among  employees  in  carrying  out  their  duties.